Separating FECG from MECG and Analyzing Fetal Heart Rate (International Journal of Innovative Research in Computer Science & Technology, 2022)
Figuring out fetal coronary heart can be  essential for monitoring the situation of a fetus. While an  ECG signal is recorded by way of putting electrodes on the  maternal stomach, the fetal ECG is regularly masked by  using the maternal ECG sign and noise. Via using an LMS  adaptive filter to extract the fetal ECG signal, after which  the use of the Pan & Tompkins algorithm to hit upon the  QRS complexes, the fetal heart may be determined with  very low errors.
Keywords: FECG; MECG; Heart rate; fetal coronary heart